Clinical Characteristics of Inflammatory Choroidal Neovascularization in a Chinese Population. (3rd May 2016) - Wu, Kunfang; Zhang, Xiongze; Su, Yu; Ji, Yuying; Zuo, Chengguo; Li, Meng; Wen, Feng
Abstract: Purpose : To describe demographic features and clinical and imaging characteristics of inflammatory choroidal neovascularization (CNV) in a Chinese population. Methods : A retrospective case review of patients with CNV secondary to uveitis from 2002 to 2013. Results : A total of 125 patients (150 eyes, 166 CNVs; bifocal CNVs in 16 eyes), 64% of whom were women, were reviewed. The mean age was 35.86 years. The proportions of patients with punctate inner choroidopathy (PIC), multifocal choroiditis (MFC), and Vogt-Koyanagi-Harada (VKH) were 50.4, 22.4, and 8%. All of the cases were classic CNV in fluorocein angiography and type 2 CNV in OCT. The proportion of subfoveal lesions in active CNV (30.09%) was less than that in inactive CNV (60.38%). Conclusions : PIC, MFC, and VKH were the three primary specific types of uveitis with inflammatory CNV in this study. Inflammatory CNV tended to break though the retinal pigment epithelium and beneath the neurosensory retina. Moreover, inflammatory CNV was usually nonsubfoveal when it occurred.